Prevalence of antibodies against Hepatitis D virus (HDV) in blood donors in Northern Germany. (June 2020) - Juhl, David; Chudy, Michael; Görg, Siegfried; Hennig, Holger
Abstract: Objective: To assess the prevalence of HDV infections in German blood donors. Method: 167 donors with acute/chronic or resolved HBV infection and detectable antibodies against Hepatitis B core antigen (anti-HBc) were tested for antibodies against HDV (anti-HDV) by competitive ELISA. Samples with detectable anti-HDV or with HBsAg and/or HBV DNA were additionally investigated for HDV RNA. Results: In nine (5.4 %) of the 167 donors, also HBsAg and HBV DNA were detectable. Anti-HDV was detectable in two of the 167 donors (1.2 %), additional four donors (2.4 %) had a borderline result. All of these donors tested negative for HBsAg and HBV DNA. Neither in samples with anti-HDV nor in HBsAg-/HBV DNA-positive samples, HDV RNA was detectable. Conclusions: At least 1.2 % of anti-HBc-positive blood donors have had an HDV infection. Although there is some evidence for a somewhat higher prevalence of HDV, the overall prevalence of HDV in Northern Germany is low.